Aplikasi Pengingat Minum Obat Di Desa Sumbersuko Kecamatan Wagir Kabupaten Malang - Rudy Mardianto (Jurnal ABM Mengabdi, 2021)
The people of Sumbersuko village in Wagir sub-district, Malang district, on average, already have an Android-based smartphone. The medication reminder application found on the smartphone is not yet known and used. The training program for 12 health cadres is expected that they understand and are able to use the medication reminder application well. Training is given to health cadres so that they can disseminate information to the community. The methods used in the training were lectures, discussions and trials with smartphones by health cadres. Beginning with the introduction of medication reminder applications, techniques for downloading applications and filling in drug data. The medication reminder application is important for people who are undergoing treatment for chronic diseases such as diabetes mellitus, tuberculosis, hypertension and other diseases who must take medication uninterruptedly. Medication reminder applications can improve adherence. Compliance with taking medication is one of the factors that affect the success of treatment, so the presence of this application is appropriate when applied. The alarm in the medication reminder application will help especially the elderly in Sumbersuko village. The presence of a medication reminder application is expected to improve people's quality of life and reduce mortality and morbidity